Cardiac αVβ3 integrin expression following acute myocardial infarction in humans. Issue 8 (7th December 2016) - Jenkins, William S A; Vesey, Alex T; Stirrat, Colin; Connell, Martin; Lucatelli, Christophe; Neale, Anoushka; Moles, Catriona; Vickers, Anna; Fletcher, Alison; Pawade, Tania; Wilson, Ian; Rudd, James H F; et al.
Abstract : Objective: Maladaptive repair contributes towards the development of heart failure following myocardial infarction (MI). The αv β3 integrin receptor is a key mediator and determinant of cardiac repair. We aimed to establish whether αv β3 integrin expression determines myocardial recovery following MI. Methods: 18 F-Fluciclatide (a novel αv β3 -selective radiotracer) positron emission tomography (PET) and CT imaging and gadolinium-enhanced MRI (CMR) were performed in 21 patients 2 weeks after ST-segment elevation MI (anterior, n=16; lateral, n=4; inferior, n=1). CMR was repeated 9 months after MI. 7 stable patients with chronic total occlusion (CTO) of a major coronary vessel and nine healthy volunteers underwent a single PET/CT and CMR. Results: 18 F-Fluciclatide uptake was increased at sites of acute infarction compared with remote myocardium (tissue-to-background ratio (TBRmean ) 1.34±0.22 vs 0.85±0.17; p<0.001) and myocardium of healthy volunteers (TBRmean 1.34±0.22 vs 0.70±0.03; p<0.001). There was no 18 F-fluciclatide uptake at sites of established prior infarction in patients with CTO, with activity similar to the myocardium of healthy volunteers (TBRmean 0.71±0.06 vs 0.70±0.03, p=0.83). 18 F-Fluciclatide uptake occurred at sites of regional wall hypokinesia (wall motion index≥1 vs 0; TBRmean 0.93±0.31 vs 0.80±0.26 respectively, p<0.001) and subendocardial infarction. Importantly, although there was no correlation with infarct size (r=0.03, p=0.90) or inflammation (C reactive protein, r=−0.20, p=0.38), 18 F-fluciclatide uptake was increased in segments displaying functional recovery (TBRmean 0.95±0.33 vs 0.81±0.27, p=0.002) and associated with increase in probability of regional recovery. Conclusion: 18 F-Fluciclatide uptake is increased at sites of recent MI acting as a biomarker of cardiac repair and predicting regions of recovery. Trial registration number: NCT01813045; Post-results.